Análisis del servicio postventa de una empresa comercializadora de productos eléctricos - Silva Ortega, Leonardo (2010)
This thesis was developed in an Ecuadorian company based in Guayaquil its main activity is to import and distribute technological items. The warranty area deals with two kinds of situations.